Development of a TaqMan Based Real-Time Fluorescent Quantitative PCR Assay for Detection of Porcine Cytomegalovirus in Semen. (10th January 2020) - Chen, Rujing; Chen, Qiuyong; Wu, Xuemin; Che, Yongliang; Wang, Chenyan; Wang, Longbai; Yan, Shan; Zhou, Lunjiang
Abstract : This study described a TaqMan based real-time fluorescent quantitative PCR (qPCR) method to detect porcine cytomegalovirus (PCMV) infection, targeting the conserved region of the DNA polymerase (DPOL) gene. The standard curve showed a linear regression relationship with a coefficient of 0.999 and a slope of y = −3.249 x + 38.958 corresponding to the amplification efficiency at 99.8%. The limit of the qPCR method was 51.9 copies/ μ l. The established qPCR method showed excellent specificity, with no cross-reaction observed with common porcine pathogens. The coefficient of variation for intra-assay and interassay variability ranged up to 1.51% and 2.24%, respectively. PCMV positive signals can be found in semen using this qPCR method, which suggested that we should pay more attention to PCMV contamination in semen in order to eliminate PCMV infection in artificial insemination and xenotransplantation.